Analysis on the Main Controlling Factors of Oil Accumulation in Putaohua Reservoir of long12 Block in Daqing Longhupao Oilfield. (27th September 2022) - Li, Tianye; Zhang, Lei; Zhang, Xuejuan; Wang, Dandan; Jin, Xiangxiong; Yin, Qianhao; Wu, Yue
Abstract : Long12 block of Longhupao oilfield is located in the western slope area of Qijia-Gulong Sag, which lay in the central depression of Songliao basin. Recent exploration and development shows that Putaohua oil layer has great potential storage. However, the block is located in the ring concave fault zone, with complex geological background and extensive low resistivity oil layers and water layers of high resistivity, resulting in an unclear condition of reservoir forming and oil-water distribution rules of Putaohua oil layer, which deeply restricts the pace of increasing storage and production of the oilfield. In this study, the data of logging, logging, drilling, analysis, and testing are adopted to study carries out a reservoir forming conditions such as source rocks, reservoirs, caprocks, traps, and migration conditions. Meanwhile this study discuss the main controlling factors of Putaohua reservoir formation in combination with the law of oil-water distribution, so as to provide a geological basis for clarifying the reservoir forming law of long 12 block and the prediction of favorable target areas.